Hubungan biaya produksi, harga jual dan etos kerja islam dengan pendapatan petani padi dengan daya produksi sebagai variabel mediasi - Fathi, Faiz Aslahul; Iskandar, Iskandar (Nur Science Institute, 2024)
This study aimed to determine the Effect of Production Costs, Selling Prices, and Islamic Work Ethics on Farmers’ Income with Production Capacity as a Mediating Variable. This study is quantitative; the object of this study is rice farmers in Ngambakrejo Village. The population is farmers in Ngambakrejo Village; the sample taken is 83 people. Data collection was carried out by distributing questionnaires. The study results indicate that income is influenced by selling prices and Islamic work ethics, Islamic work ethics influence production capacity, production capacity affects income, and only Islamic work ethics influence income through production capacity.